Seasoned speech : rhetoric in the life of the church - Beitler, James Edward, III (IVP Academic, an imprint of InterVarsity Press, 2019)
Being a faithful disciple of Christ means having seasoned speech: practicing a rhetoric that beneficially and persuasively imparts the surprising truth of the gospel. James Beitler seeks to renew interest in and hunger for an effective Christian rhetoric by closely considering the work of five beloved Christian communicators: C. S. Lewis, Dorothy L. Sayers, Dietrich Bonhoeffer, Desmond Tutu, and Marilynne Robinson.